Spatial and temporal evolution characteristics of apple carbon emissions in China, 1991–2020 - Qiangqiang Zhang; Xixi Gao; Yujie Hu; Zhongwei He; Xiaojing Li (Scientific Reports, 2025)
Abstract Articulating the spatial and temporal features of apple carbon emissions in China across different years and areas is critical for developing an appropriate and acceptable apple carbon reduction program. This paper builds a provincial-level database (1991–2020) of apple carbon emissions in China, covering six primary sources: chemical fertilizers, pesticides, plastic films, machinery, irrigation, and tillage. By using the LMDI approach, spatial autocorrelation analysis, and barycenter analysis, we find that (1) China’s apple carbon emissions exhibited an M-shaped fluctuation pattern, with a 1.38-fold increase during the study period, while apple carbon intensity increased 67.01%. (2) Chemical fertilizers were the largest contributor (55%) to apple carbon emissions, followed by plastic films, irrigation, pesticides, machinery, and tillage. (3) Apple carbon emissions showed significant regional heterogeneity, with a spatial pattern of the Bohai Bay production area as the largest in terms of carbon emissions and carbon intensity. While chemical fertilizers were the primary contributor in the other four production areas, plastic films had a disproportionately high impact in Bohai Bay production area. Moreover, 13 provinces increased their carbon emissions, while 9 provinces reduced. Chemical fertilizers, plastic films and irrigation were dominant contributing factors in 14, 5, and 3 provinces, respectively. (4) There is no significant spatial association between surrounding provinces in apple carbon emissions. Spatial correlations reveal a “high-low” or “low-high” agglomeration of negative values during certain individual years. In 2020, the barycenter of apple carbon emissions migrated southwestward 451.69 km, reaching Shaanxi Province. This article recommends promoting organic fertilizers, water-fertilizer integration, mulch recycling, straw mulching, and drip irrigation to minimize apple carbon emissions. Additionally, region-specific emission reduction strategies should be developed, with particular emphasis on Shaanxi and Gansu, considering their distinct spatial and temporal characteristics.